WAKAF PRODUKTIF DALAM PERSPEKTIF MAQASID SHARI’AH (STUDI TENTANG WAKAF PRODUKTIF DI PMDG PONOROGO) - Masruchin; A’yunina Mahanani; Diyah Ekowati (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
Wakaf is a Maliyah worship that have tight relation with development of umat welfare. It is a worship in the form of social economy. The potential of wakaf is huge nowadays however it does not use optimally yet because of some factors so that it cannot give maximum role in bringing welfare for society and empowering society’s economy. Wakaf does not only support the development of science but also prepare all facilities needed by students of university or society. Modern Boarding School Darussalam Gontor, Islamic boarding school that considered has been successful in organizing productive wakaf to finance itself and because of that, it can be the role model for developing educational institution base wakaf. Most of the result of wakaf used to develop the business and another used for teachers’ welfare and funding institutions of boarding school in shelter of PMDG. Some of the fund also donated to assistance founding of religious social life of society around. As for the concept of wakaf PMDG refers to maqashid – al shari’ah that is in level of law enforcement (tatbiq al hukmi) that is create welfare and avoid mercilessness. Trimutri in his wakaf concept more emphasizes on the welfare aspect aimed to that wakaf is a media to get closer with Allah SWT. It is form of Hajiyyat needs to possess the nature of religion, and give humanity assistance institutionally (at – tahbis), and for education of Islamic boarding school related to the intelligence development, so that it can give advantage optimally for Muslim’s life later.